2020
DOI: 10.3399/bjgp20x713393
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality in the first COVID pandemic peak: cross-sectional analyses of the impact of age, sex, ethnicity, household size, and long-term conditions in people of known SARS-CoV-2 status in England

Abstract: BackgroundThe SARS-CoV-2 pandemic has passed its first peak in Europe.AimTo describe the mortality in England and its association with SARS-CoV-2 status and other demographic and risk factors.Design and settingCross-sectional analyses of people with known SARS-CoV-2 status in the Oxford RCGP Research and Surveillance Centre (RSC) sentinel network.MethodPseudonymised, coded clinical data were uploaded from volunteer general practice members of this nationally representative network ( n = 4 413 734). All-cause m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(80 citation statements)
references
References 31 publications
3
76
1
Order By: Relevance
“…Recent work in Oxford RCGP database suggests that outcomes are similar in those with clinically probable and laboratory-confirmed cases. [17] Serology testing, if available nationally in the future could also be helpful. Our cohort is likely to reflect women with more severe COVID-19 symptoms who went for testing or made contact with a general practice for review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work in Oxford RCGP database suggests that outcomes are similar in those with clinically probable and laboratory-confirmed cases. [17] Serology testing, if available nationally in the future could also be helpful. Our cohort is likely to reflect women with more severe COVID-19 symptoms who went for testing or made contact with a general practice for review.…”
Section: Discussionmentioning
confidence: 99%
“…[10,11] Our previous work shows that clinical and probable cases are similar in terms of outcomes; for mortality, the odds ratios were 8.9 (95% CI = 6.7 to 11.8, P <0.0001) and 9.7 (95% CI = 7.1 to 13.2, P <0.0001) for RT-PCR confirmed and clinically diagnosed cases, respectively. [12]…”
Section: Methodsmentioning
confidence: 99%
“…These report COVID-19 mortality rates 2-3 fold higher than the general population,(12, 13) no difference in case-fatality,(14) overall case-fatality with OR=2.75 or OR=3.61 in the <70 year olds,(15) and all-cause mortality in those with known COVID-19 with OR=1.97. (11) A more comprehensive study on adults with intellectual disabilities, including only those in residential settings (compared with whole-community general population) reported COVID-19 infection rates to be about 4 times higher, case-fatality to be almost double, and mortality rates to be 7.8 times higher. (16) In our study of a whole nation’s adult population with intellectual disabilities, we found they were twice as likely to become infected with COVID-19, with a case-fatality 25% higher than in the general population, and COVID-19 mortality was 2.3 times higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…(8, 9) They are also more likely to live in congregate settings or be in receipt of social care (10); recent studies have reported high rates of COVID-19 mortality within multi-occupancy residences. (11) However, questions remain as to whether, compared with other people, people with intellectual disabilities are more likely to contract COVID-19, and whether they have more severe infections, and higher COVID-19 mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation